Pengaruh Strategi Diversifikasi terhadap Kinerja Keuangan pada Bank Umum Konvensional yang Terdaftar di BEI 2020-2022 - Nuryana, Yayan; Ningsih, Diah Wuriah; Murdianingsih, Dian; Melia, Saras (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
The study investigates the impact of diversification on the financial performance of commercial banks listed on the Indonesian Stock Exchange (BEI) from 2020 to 2022. Using purposive sampling techniques, the study analyzed data from 90 samples to examine the relationship between diversification strategies and measured financial performance with return on assets (ROA). Research results show that diversification has no significant impact on the financial performance of commercial banks. It shows that higher levels of diversification in banks do not always correlate with higher financial performance. On the contrary, the effects of diversification on financial performance depend on how banks manage their capital costs and maximize revenue. The study also revealed that commercial banks tend to take different approaches in implementing diversification strategies, which can vary depending on the size of the bank, business models, and market conditions. Although diversification does not have a significant direct impact on financial performance, the study emphasizes the importance of well-planned and implemented diversity strategies. The findings provide important insights for bank management and policymakers in the banking sector. Further research is suggested to explore other factors that may affect financial performance in the banking industry, including risk management practices, financing structures, and macroeconomic conditions. This research is expected to contribute to a deeper understanding of the relationship between diversification and financial performance in the Indonesian banking context. Keywords: diversification strategy, financial performance